Soundings on South Asia - Mujtaba, Syed Ali 1962- (New Dawn Press Group, 2005)
The unity in diversity that makes South Asian culture unique is discussed in these 70 articles that detail a region marked by an asymmetry of power structure, different systems of governance, and interstate conflict but at the same time exhibits a great deal of harmony in ethnic composition, food habits, language, values, mores, and norms. A compendium of the region's development, these short essays focus on individual countries within the greater South Asian context in order to understand the dynamics that block regional integration. South Asia's inability to forge a regional identity is challenged by theories that argue the differences between countries are not as large as they seem.